The Effectiveness of Android-Based Pre-Marriage Class Applications Against the Knowledge of the Prospective Bride - Dewi Sumardilah; Retno Puji Astuti; Aprina Murhan (Universitas Aisyah Pringsewu, 2023)
In 2021 a training model has been successfully developed in a classical form for prospective brides, namely the Pre-Marriage Class. And in 2022 an Android-based Pre-Marriage Class application will be developed as a learning medium. This is to answer the problem of the limited time that the bride and groom have to participate in class activities and also considering the current pandemic situation which still limits the gathering of people in one room. The research objective was to determine the effectiveness of the pre-marital class application in increasing the understanding of prospective brides and grooms about maternal and child health in the context of preventing stunting toddlers. This research is research and development in nature which is intended to produce products in the form of mobile apps (applications) for Pre-Marriage Classes. As the study population were prospective brides in Kemiling District, and the sample was determined by accident, namely prospective brides who had registered at the KUA Kemiling District until March 2022. Data collection was carried out by means of interviews, questionnaires, and pretest posttest. The analysis was carried out descriptively and analytically using the N-gain test. The results showed that the pre-marital class application was appropriate for use as a learning medium (media expert score = 87.5%, material expert score = 78.6%, health worker score = 80.4%, and the bride and groom's score = 85.3 %). The application of pre-marital classes is also effective in increasing the understanding of the bride and groom in maternal and child health (N-gain value 0.59).